Integrasi Filsafat Ilmu Dalam Pendidikan Karakter Di Lembaga Pendidikan Islam: Tantangan Dan Peran Guru - Trianti, Elis; Irawan (Yayasan Cendekia Gagayunan Indonesia, 2025)
The main focus of this research is how values such as honesty, hard work, and empathy can be instilled through effective teaching methods, including discussion, practice, and reflection. Although progress has been made in the implementation of character education, significant challenges remain, particularly related to the pressure to achieve high academic results and the lack of support from educational management. The role of teachers as role models in applying the principles of philosophy of science is also emphasized, as they can inspire students to adopt these positive values. This article concludes that collaborative efforts from all stakeholders are crucial to addressing the existing challenges and creating a balanced education between academic aspects and character, in order to produce a generation that is both intelligent and morally upright.